Meta‐analysis of Genome‐Wide Association Studies Identifies Novel Loci Associated With Optic Disc Morphology. Issue 3 (28th January 2015) - Springelkamp, Henriët; Mishra, Aniket; Hysi, Pirro G.; Gharahkhani, Puya; Höhn, René; Khor, Chiea‐Chuen; Cooke Bailey, Jessica N.; Luo, Xiaoyan; Ramdas, Wishal D.; Vithana, Eranga; Koh, Victor; Yazar, Seyhan; et al.
ABSTRACT Primary open‐angle glaucoma is the most common optic neuropathy and an important cause of irreversible blindness worldwide. The optic nerve head or optic disc is divided in two parts: a central cup (without nerve fibers) surrounded by the neuroretinal rim (containing axons of the retinal ganglion cells). The International Glaucoma Genetics Consortium conducted a meta‐analysis of genome‐wide association studies consisting of 17, 248 individuals of European ancestry and 6, 841 individuals of Asian ancestry. The outcomes of the genome‐wide association studies were disc area and cup area. These specific measurements describe optic nerve morphology in another way than the vertical cup‐disc ratio, which is a clinically used measurement, and may shed light on new glaucoma mechanisms. We identified 10 new loci associated with disc area (CDC42BPA, F5, DIRC3, RARB, ABI3BP, DCAF4L2, ELP4, TMTC2, NR2F2, and HORMAD2) and another 10 new loci associated with cup area (DHRS3, TRIB2, EFEMP1, FLNB, FAM101, DDHD1, ASB7, KPNB1, BCAS3, and TRIOBP). The new genes participate in a number of pathways and future work is likely to identify more functions related to the pathogenesis of glaucoma.